Optimization of Site-wide Heat-Integrated Utility Systems with Heat Pumps using MILP - Hochhaus, Thorben; Grünewald, Marcus; Riese, Julia (Systems and Control Transactions)
The reduction of CO2-emissions in the chemical industry is essential to meet European climate targets. Particularly, the reliance on fossil fuels for process heat supply is a key factor for CO2-emissions. Electrically driven compression heat pumps are a promising option to reduce fossil fuel consumption by upgrading low-temperature waste heat to a higher temperature level, provided that low-carbon electricity is available. However, the integration of heat pumps into chemical utility systems remains a challenge due to economic constraints and the high complexity associated with site-wide heat integration and retrofit of existing structures. This work presents a mixed-integer linear programming (MILP) approach for the optimization of utility systems with integrated heat pumps. To address computational complexity, candidate utility temperature levels are pre-selected, and feasible heat pump coefficients of performance (COP) are precomputed. The framework is applied to both greenfield and retrofit scenarios for a synthetic case study consisting of 400 process streams. In the greenfield scenario, optimal utility temperature levels and heat pump integration configurations are identified. For the retrofit scenario, temperature levels of an existing utility system are modified to reduce total annual costs (TAC). Additionally, sensitivity analysis is conducted to assess the influence of key economic and environmental parameters. The presented case studies demonstrate short solution times, highlighting the suitability of the proposed framework for screening studies and systematic sensitivity analyses in early-stage design and retrofit applications.

Development of a methodology for heat pump-based heat integration in batch processes - Wloch, Johannes; Grünewald, Marcus; Riese, Julia (Systems and Control Transactions)
Heat pumps offer the possibility of reducing CO2-emissions in the chemical industry. However, the integration of heat pumps, especially in non-continuous processes, faces several challenges. Energy storage facilitates a way to enhance heat integration by providing a continuous supply of heat flows. By doing so, the question arises as to whether this implementation should be applied to the process or to the utility level. At the process level, there is usually more freedom, as one is not bound by the existing temperature levels of the utility system, which are mostly difficult to retrofit. Therefore, this study presents an approach that generates heat integration concepts at the process level based on two different criteria. These criteria influence which process streams are grouped for a storage implementation and therefore influence the heat integration. The aim is to maintain the heat flows as continuous as possible by integrated heat storages. Finally, the possible heat integration concept is evaluated in terms of energy efficiency by a know method for continuous process streams, here the pinch analysis.

Der Logarithmus zur Bestimmung des pH-Wert-Verlaufs einer Titration: Ein fächerverbindender Unterrichtsvorschlag unter Verwendung digitaler Werkzeuge - Bender, Roland; Witte, Thomas; Hattermann, Matthias; Fechner, Sabine (Neue Materialien für einen realitätsbezogenen Mathematikunterricht)

Forum Psychomotorik: Bewegung, Spiel und Sport im schulischen Ganztag - Satzinger, Nicole; Noetzel, Ida (Motorik)

"Kirchentag" - An example of religious happenings as places for the formation of faith in a world full of diversity - Schroeter-Wittke, Harald (Religious Diversity and Global Concerns)

Intertwining theory and practice: Design of planning phases in PD training to support effective teacher planning processes - Knaudt, Katharina; Herold-Blasius, Raja; Selter, Christoph (Proceedings of the Fourteenth Congress of the European Society for Research in Mathematics Education (CERME14)

Fostering Knowledge Facets of the TPACK Framework Through Designing Digital Mathematical Escape Games – A Qualitative Content Analysis of Pre‑Service Teachers’ Self‑Reported Learnings and Challenges - Herold-Blasius, Raja; Gruhn, Katrin; Kleinschmidt, Vera; Thurm, Daniel; Tusche, Carina (International Journal of Science and Mathematics Education)

TPACK learning paths of pre-service teachers when designing digital mathematical escape games - Herold-Blasius, Raja; Kleinschmidt, Vera (Proceedings of the Nineteenth ERME Topic Conference: Connecting the Learning of Mathematics Teaching to Practice)

Digitale Escape Games in der Hochschullehre – Seminarkonzept - Herold-Blasius, Raja; Kleinschmidt, Vera

Temporal causal feature selection for robust machine learning modelling of data center operations - Zapata Gonzalez, David Ricardo; Meyer, Marcel; Zalipski, Kevin; Müller, Oliver (Applied Energy)

Defining Islamic Comparative Theology
Over the last decades, Comparative Theology has established itself in varying methodological ways while considering the reality and plurality of religions. Although Comparative Theology can be a confessional or a non-confessional endeavor, most protagonists and theorists have been Western Christians. This could lead to the conclusion that Comparative Theology is in fact a Christian undertaking and implicitly or explicitly bound to conceptions like Christology. Furthermore, it could be argued that there is a certain asymmetry of power in the discourse between religions when the parameters of Comparative Theology are defined mainly by Christian theologians. This volume aims to be the first step to programmatically and conceptionally explore the possibility of a genuinely Islamic Comparative Theology in a constructive endeavor. This endeavor should neither be misunderstood as an apologetic questioning of the status quo in Comparative Theology nor as a project that deconstructs Comparative Theology. Rather, by searching for new approaches from the Islamic traditions it opens up ways and forms of learning, hermeneutically complementary with prominent attitudes, methods in Comparative Theology.
Keywords: Comparative Theology; Islamic Theology; Islamic Comparative Theology

Chapter 5 Covenant Theology in the Qur’an—Challenges and Insights for Comparative Theology from a Muslim Perspective - Ghaffar, Zishan (Defining Islamic Comparative Theology)
Keywords: Covenant Theology; Qur'an; Comparative Theology; Islamic Comparative Theology

History and political Theology: The term khalīfah in the Qur’an - Ghaffar, Zishan (Journal of the International Qur’anic Studies Association)
This article examines the use of the Arabic term khalīfah in the Qur’an through the lens of its implicit historical-political theology. To achieve this, the study employs a comparative analysis of the concept of vicarious kingship within the Syriac tradition. The findings suggest that the Qur’an rejects the notion of a historical replacement or substitution of believing individuals or groups with new ones. Furthermore, it challenges the framework of a political theology that envisions the typological and eschatological fulfillment of messianic rulership. Instead, the term khalīfah primarily emphasizes the inherently political nature of humanity, in which each individual is continuously accountable to their Creator.

Empirische Studien zur Demokratiebildung im Lehramtsstudium in Nordrhein-Westfalen - Wehde, Janis

Local strong solutions in a quasilinear Moore-Gibson-Thompson type model for thermoviscoelastic evolution in a standard linear solid - Claes, Leander; Winkler, Michael (Nonlinear Differential Equations and Applications NoDEA)

Selection of the mini- and micro-channels geometry for improved heat recuperation in specific industrial conditions - Kapustenko, Petro; Tovazhnyanskyy, Leonid; Arsenyeva, Olga; Riese, Julia; Varbanov, Petar Sabev (International Journal of Thermal Sciences)

Building Bridges – Partizipation und Reflexion mit der LEGO® SERIOUS PLAY®-Methode fördern - Breuing, Friederike

Error estimates for $A$-stable backward difference full discretizations of Willmore flow of closed surfaces - Bullerjahn, Nils; Kovács, Balázs (ArXiv)

The Lord’s Prayer and its place in the London Underground. Reflections on religious diversity and a parody based on a central sacred text - Breckner, Anne (Religious Diversity and Global Concerns)

Die Widerruflichkeit der Verbraucherbürgschaft – a never ending story - Bartlitz, David (JuristenZeitung)
Die Frage, ob bei einer Verbraucherbürgschaft, die in einer Außergeschäftsraumsituation abgegeben worden ist, ein Wider-rufsrecht besteht, ist seit nunmehr 30 Jahren umstritten. Der BGH hatte im Jahr 2020 in einem Grundsatzurteil das Widerrufsrecht abgelehnt - nur neun Monate vor der erneuten Ände-rung des für diese Frage entscheidenden § 312 BGB. Der Beitrag zeigt, dass die Abgabe einer Bürgschaftserklärung notwendigerweise mit der Bereitstellung personenbezogener Daten verbunden ist. Dies eröffnet aufgrund des überobligatorisch weit gefassten Tatbestands des neuen § 312 Abs. 1a BGB den Anwendungsbereich des Verbrauchervertragsrechts und begründet damit das Widerrufsrecht nach § 312g BGB.